Laser Generated MoS2 Nanomaterials and Its Applications: A Review - Jasim, Layal A.; Rajab, Fatema H.; Alshaer, Ahmad W. (Al-Nahrain Journal for Engineering Sciences, 2025)
This review study emphasizes the significance of MoS2 nanomaterials, their manufacture, and their applications. This review examined nanomaterials and their generation processes, concentrating on laser ablation and nanomaterial production. This study advances nanomaterial synthesis and helps discover new applications by explaining the fundamental concepts and aspects affecting synthesis. Future studies should optimize laser settings, explore novel precursor materials, and understand laser-induced MoS2 synthesis pathways to enable customized nanomaterial design and engineering.